Peasant Land Tenure with Rent in the Western Territory of the Russian Empire and Legislative Attempts to Eliminate it (Second Half of the 19th - Early 20th Centuries) - A. A. Ivanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The issue of peasant land tenure with rent in the Russian Empire and attempts to eliminate it in the second half of the XIX - early XX centuries is considered. Attention is paid to the activities of the Russian authorities aimed at legislatively resolving problems related to the peculiarities of land tenure relations with rent in the Western Territory. The relevance of the study is due to the need to summarize the material accumulated by historiography on this topic, as well as the lack of elaboration of plots related to attempts by representative institutions of the beginning of the 20th century - the State Duma and the State Council - to eliminate or even to streamline the peasant land tenure with rent relations in the Russian Empire. The novelty of the study is in reviewing of the new sources, allowing to enter into scientific circulation data that clarify the idea of measures to regulate the rule of peasant land tenure with rent in the reign of Emperor Nicholas II. Particular attention is paid to the consideration by the State Duma and the State Council of draft laws on the right to development and “On common ownership in cities and towns of Western and Belarusian provinces”, designed to regulate peasant land tenure with rent interests. It has been proved that the initiative of the State Duma to eliminate the rest of the peasant land tenure with rent in the Western Territory has not actually been implemented.